Protection of the population health from electromagnetic hazards − challenges resulting from the implementation of the 5G network planned in Poland - Marek Zmyślony; Paweł Bieńkowski; Alicja Bortkiewicz; Jolanta Karpowicz; Jarosław Kieliszek; Piotr Politański; Konrad Rydzyński (Nofer Institute of Occupational Medicine, 2020)
There is an ongoing discussion about electromagnetic hazards in the context of the new wireless communication technology - the fifth generation (5G) standard. Concerns about safety and health hazards resulting from the influence of the electromagnetic field (EMF) emitted by the designed 5G antennas have been raised. In Poland, the level of the population's exposure to EMF is limited to 7 V/m for frequencies above 300 MHz. This limitation results from taking into account the protective measures related not only to direct thermal hazards, but also to diversified indirect and long-term threats. Many countries have not established legal requirements in this frequency range, or they have introduced regulations based on recommendations regarding protection against direct thermal risks only (Council Recommendation 1999/519/EC). For such protection, the permissible levels of electric field intensity are 20-60 V/m (depending on the frequency). This work has been created through an interdisciplinary collaboration of engineers, biologists and doctors, who have been for many years professionally dealing with the protection of the biosphere against the negative effects of EMF. It presents the state of knowledge on the biological and health effects of the EMF emitted by mobile phone devices (including millimeter waves which are planned to be used in the 5G network). A comparison of the EU recommendations and the provisions on public protection being in force in Poland was made against this background. The results of research conducted to date on the biological effects of the EMF radiofrequency emitted by mobile telecommunication devices, operating with the frequencies up to 6 GHz, do not allow drawing any firm conclusions; however, the research evidence is strong enough for the World Health Organization to classify EMF as an environmental factor potentially carcinogenic to humans. At the moment, there is a shortage of adequate scientific data to assess the health effects of exposure to electromagnetic millimeter waves, which are planned to be used in the designed 5G devices. Nevertheless, due to the fact that there are data indicating the existence of biophysical mechanisms of the EMF influence that may lead to adverse health effects, it seems necessary to use the precautionary principle and the ALARA principle when creating environmental requirements for the construction and exploitation of the infrastructure of the planned 5G system. Med Pr. 2020;71(1):105-13